2015
DOI: 10.1039/c5md00308c
|View full text |Cite
|
Sign up to set email alerts
|

Inspired by magnolol: design of NSAID-based compounds with excellent anti-inflammatory effects

Abstract: A10 was selected to elucidate the anti-inflammatory mechanism at the transcriptional level, suggesting its potential to serve as a novel anti-inflammatory agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Compound 12 was more effective (up to 90 %) than magnolol in reducing terephthalic acid-induced ear edema (58.3 %) at 0.75 μM. [20]…”
Section: Replacing the Magnolol Hydroxy Groups With Mercapto Moietiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Compound 12 was more effective (up to 90 %) than magnolol in reducing terephthalic acid-induced ear edema (58.3 %) at 0.75 μM. [20]…”
Section: Replacing the Magnolol Hydroxy Groups With Mercapto Moietiesmentioning
confidence: 90%
“…The results demonstrated that Compound 12 reduced the production of IL‐1, IL‐6, and TNF‐ ɑ caused by TPA via the inhibitor of the kappa B kinase/nuclear factor kappa B signaling pathway and significantly reduced the average weight of mouse ear punches. Compound 12 was more effective (up to 90 %) than magnolol in reducing terephthalic acid‐induced ear edema (58.3 %) at 0.75 μM [20] …”
Section: Magnolol Structural Modifications and Biological Actionsmentioning
confidence: 99%
“…According to our previous publication, the concentration at which the initial screening anti-inammatory activities of N and M were conducted was selected as 0.75 mM. 20 As shown in Fig. 2, ear oedema was induced by the topical application of TPA alone.…”
Section: Effects Of Naproxen In Combination With Magnolol On Tpa-indu...mentioning
confidence: 99%
“…Naproxen is one type of NSAID used for the treatment of inflammatory diseases, such as inflammatory bowel and rheumatic diseases, as well as myocarditis [16]. Current studies have revealed that naproxen combined with natural compounds, or structurally modified naproxen with active compounds derived from natural products are beneficial to enhance their bioactivity [17][18][19][20]. As shown in Figure 1a,b, it has been suggested that a naproxen derivative containing curcumin or magnolol reduced phorbol-12-myristate-13-acetate (TPA)-induced skin inflammation in a TPA-induced mouse ear edema model.…”
Section: Introductionmentioning
confidence: 99%